Pengaruh Metode Pembelajaran Demonstrasi Terhadap Hasil Belajar Siswa Kelas X pada Mata Pelajaran Fiqih - Sarfiah, Sarfiah; Wibawa, Restu; Purmadi, Ary (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2021)
The purpose of this study was to determine the effect of the demonstration learning method on the learning outcomes of class X students in fiqh subjects at Madrasah Aliyah Hidayatullah Mataram in the 2020/2021 academic year. This research is a quantitative research using a two-group post test design type of experiment. The data collection technique in this study used the test as the main method with observation and documentation as a complementary method using the t-test formula. The population in this study amounted to 55 students. The sampling technique used in this research is random sampling with a total of 55 students. In accordance with the results obtained, the t-count is smaller than the t-table value (1.714 < 2.101) which means Ho is accepted and Ha is rejected which reads: there is no effect of demonstration learning methods on the learning outcomes of class X students in fiqh subjects in Madrasahs Aliyah Hidayatullah Mataram, which is due to the limited time of class hours and there are still many students who do not concentrate and pay less attention to the teaching and learning process in the classroom.